The interplay between autophagy and tumorigenesis: exploiting autophagy as a means of anticancer therapy. (2nd May 2017) - Lorente, Juan; Velandia, Carolina; Leal, Jose A.; Garcia‐Mayea, Yoelsis; Lyakhovich, Alex; Kondoh, Hiroshi; LLeonart, Matilde E.
ABSTRACT: In wild‐type cells, autophagy represents a tumour‐suppressor mechanism, and dysfunction of the autophagy machinery increases genomic instability, DNA damage, oxidative stress and stem/progenitor expansion, which are events associated with cancer onset. Autophagy occurs at a basal level in all cells depending on cell type and cellular microenvironment. However, the role of autophagy in cancer is diverse and can promote different outcomes even in a single tumour. For example, in hypoxic tumour regions, autophagy emerges as a protective mechanism and allows cancer cell survival. By contrast, in cancer cells surrounding the tumour mass, the induction of autophagy by radio‐ or chemotherapy promotes cell death and significantly reduces the tumour mass. Importantly, inhibition of autophagy compromises tumorigenesis by mechanisms that are not entirely understood. The aim of this review is to explain the apparently contradictory role of autophagy as a mechanism that both promotes and inhibits tumorigenesis using different models. The induction/inhibition of autophagy as a mechanism for cancer treatment is also discussed.